Influence of the environmental conditions and academic performance in the Primary Education classrooms of Iberoamerica. - Murillo, F. Javier; Martinez-Garrido, Cynthia (Education Policy Analysis Archives, 2012)
School climate describe the environment that affects the behavior of teachers and students at the classroom. Elements of the school climate such as the building and its arrangements reflect the children, their needs, and their educational accomplishments. Some of these elements, however, have not received much attention in studies about the academic performance in Primary Education. This paper describes the relationship between environmental conditions in the classroom (e.g., lighting, isolation, order, cleanliness,…) and the academic performance of the students. This study analyses 248 Primary Education classrooms from nine countries of Iberoamerica using a 4-level Multilevel Model. The following information sources were used in this study: i) Classroom guide observation completed by researcher. ii) Standardized test to Math and Language learning. iii) Questionnaire to classroom teachers, pupils and their families. The results of this study highlight the strong influence of the order and cleanliness on the academic performance of the students.